Peningkatan Kemampuan Berbahasa Lisan Menggunakan Metode Dramatisasi pada Siswa Kelas X SMA Negeri 7 Bandar Lampung - Rachmasisca, Frieska Maryova; Rohana, Rohana; Dedi, Fransisca S.O.; Elsapitri, Mutiara (LPPM STKIP PGRI Bandar Lampung, 2024)
Speaking skills relate to human speech organs that are verbally spoken. Oral language can also determine movements that correspond to the words produced by the speech apparatus. We can combine learning about spoken language by using the dramatization method. This method is a learning activity by staging a story situation from a point of view played by students. By playing roles, students are able to pronounce the words as well as possible so that the message in the story the students act out is conveyed well. This method is considered suitable because it has advantages, including making learning more fun, students interacting with each other in playing existing characters. It also fosters students' critical thinking in determining the message implied in the story. The problem that occurs in the field is that students are less interested in learning because they use methods that are still conventional and that's all. Lack of student concentration in unfocused learning. Students have not been able to solve the problems posed by the teacher as a group. The aim of this research is to improve oral language learning using the dramatization method. Using this learning method in class so that students can understand the roles of characters so that students are able to tolerate them. Learning is more fun by using this dramatization method. The results of this research showed an improvement from cycle I to cycle II. In cycle I there was an increase, namely the average student score in classical was 50.5% with the percentage of classical completion and cycle 2 reaching 83%.